Evaluasi Metadata Rekam Medis Elektronik Rawat Jalan - Sumadi, Andrias Feri; Sinanto, Rendi (Indonesian Health Issue, 2025)
Background: In today's digital era, electronic medical records (EMR) play an important role in improving the quality of health services. Objective: This study focuses on the evaluation of outpatient electronic medical record metadata at Puskesmas Bantul II, Yogyakarta, with the aim of ensuring the compliance of metadata with the regulations of the Ministry of Health of the Republic of Indonesia, KEPMENKES HK.01.07/MENKES/1423/2022. Method: This study uses a qualitative method with a case study approach to gain an in-depth understanding of the process and challenges in managing and evaluating EMR metadata at Puskesmas Bantul II. Results: The results of the study showed several metadata discrepancies that require continuous adjustment and evaluation. This study aims to identify variables and metadata in SIMPUS, calculate the percentage of conformity of variables and metadata, and reveal the factors causing the discrepancies. Conclusion: It is expected that the results of this study can improve the efficiency and effectiveness of health services at Puskesmas Bantul II and ensure compliance with data security standards and patient privacy.